Analisis Sistem Persaingan Bisnis Kuliner Dapur Sumba - Sihang Gregorius Balimema (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
The culinary industry in Sumba is experiencing rapid growth with increasing tourist interest in the uniqueness of local cuisine. One of the culinary business actors that is growing is Dapur Sumba, which is facing competition with other culinary businesses. This study aims to analyze the culinary business competition system of Dapur Sumba using the Porter's Five Forces approach, which includes the threat of new entrants, supplier bargaining power, consumer bargaining power, threat of substitute products, and intensity of competition in the industry. The research method used is a qualitative approach with data collection techniques through interviews, observations, and literature studies related to the local culinary industry. The results of the study show that Dapur Sumba's competitiveness is influenced by the uniqueness of the menu based on local ingredients, competitive pricing strategies, and the effectiveness of digital marketing. However, the threat from new entrants and substitute products is still a challenge that needs to be anticipated. Based on the analysis conducted, the recommended strategy to increase Dapur Sumba's competitiveness is increasing product innovation, strengthening branding, and optimizing digital marketing through social media and e-commerce platforms. In conclusion, a deep understanding of competition factors and adaptive business strategies will help Dapur Sumba maintain and improve its position in the local culinary industry in Sumba.